The effect of promotion means in the developing the activity of financial markets: A case study of Iraqi stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The promotion by its means lead a vital and important role at the level of all organizations, whether (industrial or service) in general, and financial markets in particular. The promotion is earns delved to be as one of the main operations which  market uses it through various means of financial markets and companies which its shares listed in the aim of (finance or investment), with a view to the implementation and financing of public and private projects the one hand, or with a view to achieving profits through investment of speculative or... For other purposes, on the other hand.Accordingly, we find that the set of public and private goals joint between the financial markets and listed companies respectively, will serve the strategic objectives for each of them, and here is achieved integration and interaction between available resources and the possibility of exploiting a manner that achieves the best, which reflected its impact on development activity and investment in the financial markets (market securities) on one hand, and economic development on the other. The results of research confirmed that there is a set of internal and external determinants involving the Iraq stock exchange market  with listed companies that affect the use of means promoting of related to the law of the market and other possibilities available and degree of cooperation of listed companies to promote itself and the market, and it recommended that research the need for responsible parties in the Iraq stock exchange adopt a statute or law to stimulate the use of promotional tools are required companies in which to promote and provide the ways and possibilities of human and financial all to promote the market to create awareness of the social, cultural and economic attracts individuals from (financiers and investors) and will lead to interaction and integration between all parties mentioned previously, which reflects its impact in increasing the volume of trading in securities and raise activity and efficiency of the securities market.